2019
DOI: 10.1002/app.48813
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐bonding assembly of heteropolyacid and poly(vinyl alcohol) for strong, flexible, and transparent UV‐protective films

Abstract: Although many preparation approaches have been developed, it remains a huge challenge to achieve ultraviolet (UV)‐protection films that combine high transparency, excellent UV‐shielding, and mechanical properties. Herein, we demonstrate a facile and eco‐friendly process for fabricating strong, flexible, and transparent UV‐protective poly(vinyl alcohol) (PVA) films by exploiting silicomolybdic acid (SiMoA) as UV absorber and reinforcing phase. Fourier‐transform infrared analysis confirms the formation of strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…This phenomenon occurs because the introduction of carboxyl groups and cross-linking significantly reduces crystallinity. Meanwhile, the diffraction peaks further decrease after the addition of GA, suggesting that the crystallinity of the composite films decrease because of the formation of hydrogen-bonds between GA and PVA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon occurs because the introduction of carboxyl groups and cross-linking significantly reduces crystallinity. Meanwhile, the diffraction peaks further decrease after the addition of GA, suggesting that the crystallinity of the composite films decrease because of the formation of hydrogen-bonds between GA and PVA …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the diffraction peaks further decrease after the addition of GA, suggesting that the crystallinity of the composite films decrease because of the formation of hydrogen-bonds between GA and PVA. 37 3.3. Swelling Ratio, Water Solubility, and Water Contact Angle.…”
Section: Resultsmentioning
confidence: 99%
“…Another approach showed that specific interactions between the polymer matrix and the NPs resulted in improved UV shielding and tensile strength. 151 The authors chose silicomolybdic acid (SiMoA) (containing an oxygen group) as the UV-absorbing NP and PVA as the matrix. The PVA/SiMoA composite was fabricated using solution casting.…”
Section: Solution Castingmentioning
confidence: 99%
“…30,31 On the other hand, PVA has high ultraviolet (UV) radiation transmittance, so it is not suitable for UV-protective material as used alone. 32 Numerous studies have been conducted on the development of UV-protective PVA products in order to increase the UV-shielding ability of PVA. Modifying the properties of PVA-based materials through blending with specific fillers is a straightforward and efficient method.…”
Section: Introductionmentioning
confidence: 99%